Role of Communication Climate on Readiness for Change Academic Staff University in Facing Higher Education Governance Changes - Neka Erlyani; Yunisa Saphira; Rahkman Ardi; Fendy Suhariadi (International Journal Labs, 2022)
Society era 5.0 makes universities face complex and dynamic competitive challenges. Universities need to change governance to become more autonomous so they might be competitive and innovative in educational services. Academic staff must be ready to face the demands of changes in educational services and administrative tasks. Readiness for change is an overall attitude influenced by individual and environmental factors. The crucial step taken in achieving change readiness is communicating a change message represented as a communication climate. Communication climate is a merger of internal organization employees' shared perceptions containing relationships quality, the openness of communication and involvement in the organization. This study aims to determine the role of communication climate on readiness for change in academic staff to face the changes in the governance of universities. A quantitative design was utilized to collect the data. Academic staff from one of the state universities in South Kalimantan (n = 277) were participated using a simple random sampling. The measuring instruments used are readiness for change scale from Holt (α = 0.94, α = 0.82, α = 0.87, α = 0.66 for each dimension) and Neill’s communication climate scale (α = 0,86, α = 0,85) which are analyzed using simple regression. The results indicate that the communication climate plays a significant role in the readiness for change of academic staff (ß= 0.330; p < .001). Therefore, the communication climate needs attention to be maintained for change readiness in the academic staff at the University